A survey on the use of electronic resources in the University of the Philippines College of Science Library and its effect on user's information needs. - Beliran, Joan M. (2006)
This study was conducted to identify the particular forms of electronics resources preferred by the users when looking for information; to compile a list on most commonly used electronic resources; to determine the purposes and reasons for using electronic resources; to find out the difficulties and problems encountered while assessing these electronic resources; and to find out how useful are the information they derived using electronic resources.